2016
DOI: 10.18052/www.scipress.com/ijppe.2.20
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Therapeutic Ability of Gut Microbiota upon <i>V. parahaemolyticus </i>Infected Farm Prawn

Abstract: Glycogen content of the prawn muscles from the three groups showed increasing trend after 30 days of feed supplementation. In control animals recorded maximum of 2.2 mg/g, and inB. coagulanssupplemented animals it was 4.1 mg/g and 3.6 mg/g inB. firmussupplemented animals increase in glycogen content in relation with feed supplementation with probiotic bacteria was most prominent in prawns. The increase in alpha amylases content may be attributed to the influence of the probiotic strain which possess exoenzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The best result was derived by bacillus isolated from intestine of sturgeon and in concentration supplementation about 6.1 log colony unit in each g diet, while bacillus and commercial lactobacillus significantly. In this course, Balcazar et al in 2007, Mahmoud et al (2015 and Rengasamy et al in 2016 suggested that the different performance of probiotic bacteria can depends on parameters such as genetics, feeding and environmental factors [4,22,23]. Also, Bairagi et al in 2002 emphasized that lipolithic, amilolithic and proteolitic activities of probiotic bacteria increase food absorption and digestion in host intestine and as a results, growth and nutrition parameters are improved [24].…”
Section: Discussionmentioning
confidence: 99%
“…The best result was derived by bacillus isolated from intestine of sturgeon and in concentration supplementation about 6.1 log colony unit in each g diet, while bacillus and commercial lactobacillus significantly. In this course, Balcazar et al in 2007, Mahmoud et al (2015 and Rengasamy et al in 2016 suggested that the different performance of probiotic bacteria can depends on parameters such as genetics, feeding and environmental factors [4,22,23]. Also, Bairagi et al in 2002 emphasized that lipolithic, amilolithic and proteolitic activities of probiotic bacteria increase food absorption and digestion in host intestine and as a results, growth and nutrition parameters are improved [24].…”
Section: Discussionmentioning
confidence: 99%
“…The best result was derived by bacillus isolated from intestine of sturgeon and in concentration supplementation about 6.1 log colony unit in each g diet, while bacillus and commercial lactobacillus significantly. In this course, Balcazar et al in 2007, Mahmoud et al (2015) and Rengasamy et al in 2016 suggested that the different performance of probiotic bacteria can depends on parameters such as genetics, feeding and environmental factors [4,22,23]. Also, Bairagi et al in 2002 emphasized that lipolithic, amilolithic and proteolitic activities of probiotic bacteria increase food absorption and digestion in host intestine and as a results, growth and nutrition parameters are improved [24].…”
mentioning
confidence: 99%